2013
DOI: 10.1242/dev.091157
|View full text |Cite
|
Sign up to set email alerts
|

Notch and Nodal control forkhead factor expression in the specification of multipotent progenitors in sea urchin

Abstract: SUMMARYIndirect development, in which embryogenesis gives rise to a larval form, requires that some cells retain developmental potency until they contribute to the different tissues in the adult, including the germ line, in a later, post-embryonic phase. In sea urchins, the coelomic pouches are the major contributor to the adult, but how coelomic pouch cells (CPCs) are specified during embryogenesis is unknown. Here we identify the key signaling inputs into the CPC specification network and show that the forkh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 57 publications
5
43
0
Order By: Relevance
“…Voronina et al, 2008;Juliano and Wessel, 2009; and data not shown). At present, it is unknown what regulates Vasa expression in these late larvae, but recent work (Materna et al, 2013) suggests that the transcription factor FoxY controls the multipotency of coelomic pouch cells, and that, in turn, FoxY is activated by Delta/Notch signalling, beginning in the 16-cell stage.…”
Section: Vasa Is Expressed In Multiple Cell Lineages During Developmentmentioning
confidence: 99%
“…Voronina et al, 2008;Juliano and Wessel, 2009; and data not shown). At present, it is unknown what regulates Vasa expression in these late larvae, but recent work (Materna et al, 2013) suggests that the transcription factor FoxY controls the multipotency of coelomic pouch cells, and that, in turn, FoxY is activated by Delta/Notch signalling, beginning in the 16-cell stage.…”
Section: Vasa Is Expressed In Multiple Cell Lineages During Developmentmentioning
confidence: 99%
“…Establishing left-right asymmetry therefore presents a crucial step in the development of the sea urchin. Several studies have examined the mechanisms behind left-right asymmetry in the sea urchin and have identified a conserved cohort of molecules including Nodal, BMP, Delta and Hedgehog providing a unique insight into the evolution of left-right axis determination (Bessodes et al, 2012; Duboc et al, 2005; Luo and Su, 2012; Walton et al, 2009; Materna et al, 2013; Su, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…All orthologous and/or paralogous TFs in Amphimedon, Acropora, Haliotis, Balanoglossus, Strongylocentrotus, and Herdmania were identified based on the shared Homology Groups (HG) with known TFs from humans (Vaquerizas et al 2009), Strongylocentrotus (Dobias et al 1996, Kontrogianni-Konstantopoulos et al 1996, Materna et al 2013, Burke et al 2006, Fernandez-Guerra et al 2006, Sodergren et al 2006, McCauley et al 2010, Sharma and Ettensohn 2010, Peter and Davidson 2011, Tu et al 2012, Yazaki et al 2014, Varrella et al 2016,…”
Section: Despite the Lack Of Orthology Between Differentially Expressmentioning
confidence: 99%
“…In Haliotis, I recovered many genes containing chitin-related protein domains, which is a known component of molluscan shells (Peters 1972, Jackson et al 2010a, and may also play important enzymatic or signaling functions in other molluscs (Schönitzer and Weiss 2007). In Strongylocentrotus, I found an overrepresentation of DEGs containing the DSL (Delta serrate ligand; PF01414) domain, along with EGF (PF00008) and ANK (Ankyrin repeat; PF13606) domains that together make up essential components of the Notch signaling receptors (Gazave et al 2009, Kopan andIlagan 2009), which has a well-established role in sea urchin endomesoderm gene regulatory networks (GRNs; Sweet et al 1999, Materna et al 2013. Additionally I found an enrichment of the asparagine synthase domain (PF00733), which is presumably responsible for making asparagine -an essential component of sea urchin skeleton (Farach-Carson et al 1989).…”
Section: Metamorphosis Is Characterized By Phylum-specific Genes: Evimentioning
confidence: 99%
See 1 more Smart Citation